Structural Characterization of 7-Chloro-4-(4-methyl-1-piperazinyl)quinoline Monohydrate - Silvia Rizzato; Francesco Marinoni (Molbank, 2025)
The crystal structure of the hydrated form of 7-chloro-4-(4-methyl-1-piperazinyl)quinoline (BPIP) was determined by single-crystal X-ray diffraction analysis. This study revealed a one-dimensional supramolecular network stabilized by hydrogen bonding interactions between BPIP and water molecules. This compound represents one-half of a piperaquine molecule, a member of the 4-aminoquinoline class of antimalarial treatments, currently employed as a partner agent in modern combination therapies. As a simplified structural analog, BPIP can serve as a critical model system for probing the intermolecular interactions, physicochemical properties, and structural behavior of the parent compound. As a result, conducting a thorough solid-state characterization of BPIP is critical for gaining insight into its physical properties and verifying the material’s identity and purity.